ANALISIS NILAI TAMBAH PENGOLAHAN KOPI ARABIKA KINTAMANI BANGLI - Yoga Priantara, I Dewa Gede; Mulyani, Sri; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 4 (2016): Desember, 2017)
Coffee is one of the main commodity than 40 national commodities and is the competitive commodities in Bali. Bangli Regency are the regency with the highest total arabica coffee production in Bali with total production of 2.476,541 tons. Of the four district in Bangli, the district of Kintamani has the highest arabica coffee production amounted to 2.314 tons. The role of government policy in the increased development of plantations not only to increase production but is more geared to increasing value added . The added value gained from the development of processed products are much higher when compared to primary products. This study aims to determine the added value of the processing of arabica coffee in any processed products. This research was conducted in the district of Kintamani, Bangli Regency in March until April 2016. Selected respondent, namely 15 units of processing in the area of Kintamani. The analysis used analysis of the value-added method Hayami of processing Hs coffee, Ose coffee and coffee powder. Advantages of this method is the ease of use and provide comprehensive information for businesses and investors.  The results showed that the added value obtained from processing Hs coffee Rp. 9.918 / kg, Ose coffee generated added value Rp. 40.749 / kg and coffee powder obtain added value Rp. 118.057 / kg. Keywords : Arabica coffee, value-added, Hayami method
Keywords: 118